A abordagem de gestão do conhecimento : um estudo exploratório em empresas petroquímicas no pólo petroquímico de Camaçari - Sá, Elizete Pereira de (2004)
The purpose of this work is to investigate and explain the knowledge management practices adopted by the petrochemical companies established in the Petrochemical Center of Camaçari, Bahia. When forming the theoretic groundwork, we focused on reviewing literature on knowledge management. Among the issues addressed, the prime issues are: the difference between data, information and knowledge; the types of knowledge; the knowledge management concept; conversion processes; and knowledge and intellectual asset development. Other related issues are also addressed, such as: organizational culture; organizational training; and information technology for supporting knowledge management. In addition to theoretic reasoning, we tried to demonstrate the main features of the petrochemical area and provide a brief background on the petrochemical industry s development process in Brazil. In order to achieve our intended goal, we conducted a field poll in the environmental protection company and in 16 petrochemical companies. The tool used for gathering data was a questionnaire with questions to be answered by the individuals who are heading the knowledge management efforts and projects in the companies included in the research.The poll shows that companies adopt various endeavors and knowledge management practices. However, knowledge management was not found to be a comprehensive and ongoing processes. The poll bears out that having knowledge management projects focus on information technology tools is a grave mistake.